Degradable material for mine ecological restoration and mine ecological restoration method
By using degradable materials prepared by alcohol derivatives and γ-polyglutamate materials, the problem of non-degradability of traditional mine ecological restoration materials is solved, and effective soil repair and environmental sustainability protection are achieved in the mine area.
Patent Information
- Application Number
- CN202411864575.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
Traditional mining ecological restoration materials are non-degradable, resulting in environmental pollution and waste of resources, and cannot meet the current demand for sustainable development.
The degradable material consisting of polycaprolactone, γ-polyglutamate, microbial bacterial agent, bentonite and pure wood fibers is prepared by esterification cross-linking of alcohol derivatives and γ-polyglutamate to form a material with good mechanical properties and degradability.
This material can gradually degrade under specific environmental conditions, degrade organic pollutants in the soil, adsorb and solidify heavy metal ions, improve the soil, promote the natural recovery of the soil, and solve the problem of soil pollution in the mining area.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ecological modification, in particular to a degradable material for mine ecological restoration and a mine ecological restoration method. Background Art
[0002] In today's society, mine ecological restoration has become a top priority, and traditional restoration materials can no longer meet current needs; first, with the large-scale exploitation of mineral resources, mining land has suffered great damage. Open-pit mining has caused a large amount of vegetation to be removed, the topsoil to be stripped, and the land has become barren and susceptible to erosion; underground mining has caused the ground to collapse, forming large areas of potholes, which seriously affected the stability and availability of the land; at the same time, the waste slag and tailings generated during the mining process are piled up like mountains, which not only occupy a large amount of land resources, but may also contain harmful substances such as heavy metals, causing pollution to the surrounding soil and water.
[0003] In addition, traditional mine ecological restoration materials are often non-degradable, such as concrete and plastic. Although these materials can fix soil and prevent soil erosion to a certain extent, their long-term presence in the environment will hinder the natural recovery of soil and the reconstruction of the ecosystem; moreover, the production and use of non-degradable materials will consume a lot of energy and resources, which is not in line with sustainable development. In view of this, we propose a degradable material for mine ecological restoration. Summary of the invention
[0004] The purpose of the present invention is to provide a degradable material for mine ecological restoration to solve the problems raised in the above background technology. For example, one of the purposes of the present invention is to treat soil pollution problems in mining areas, such as degrading organic pollutants in the soil and adsorbing and solidifying heavy metal ions; the second purpose of the present invention is to achieve ecological restoration in mining areas; the third purpose of the present invention is to provide a new type of environmentally friendly degradable material for soil restoration.
[0005] To achieve the above objectives, the present invention provides a degradable material for mine ecological restoration.
[0006] The degradable material is prepared from the following raw materials in parts by weight: 30-50 parts by weight of polycaprolactone, 10-20 parts by weight of γ-polyglutamate, 5-10 parts by weight of microbial agent, 20-30 parts by weight of bentonite and 10-20 parts by weight of pure wood fiber;
[0007] The γ-polyglutamate is prepared by esterifying and cross-linking γ-polyglutamic acid with alcohol derivatives, and the mass ratio of γ-polyglutamic acid to the alcohol derivative is 1:1-3.
[0008] Preferably, the specific preparation method of the γ-polyglutamate is as follows:
[0009] S1.1, weigh the following raw materials in parts by weight respectively: 10-20 parts by weight of γ-polyglutamic acid, 10-60 parts by weight of alcohol derivatives, 1-3 parts by weight of catalysts, 5-10 parts by weight of glycine, 1-3 parts by weight of gardenia glycoside crosslinking agent, and 10-20 parts by weight of dimethyl sulfoxide solvent;
[0010] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, setting the temperature of the magnetic stirrer to 50-80°C, stirring at a speed of 200-500 rpm for 1-3 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0011] S1.3, dissolving alcohol in glycine, placing in a magnetic stirrer, and adjusting the pH of the alcohol and glycine mixed solution to 9-10 with 0.5-1 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 30-60°C, stirring at a speed of 200-400 rpm for 2-4 hours to obtain alcohol derivatives; the alcohol itself does not have the ability to directly cross-link with gardenia glycoside and γ-polyglutamic acid, and after glycine amination, the amino group (-NH 2 ) functional group, which enables esterification and cross-linking reaction with gardenia glycoside and γ-polyglutamic acid;
[0012] S1.4, add the alcohol derivative to the γ-polyglutamic acid solution at a rate of 10-20 drops / minute, add the catalyst and the gardenia glycoside cross-linking agent at the same time, and keep stirring; by slow dripping and continuous stirring, the reaction rate can be controlled to prevent local overheating and avoid excessive reaction leading to degradation of γ-polyglutamic acid or other adverse effects;
[0013] S1.5, the mixed solution of S1.4 is heated to reflux at 60-100°C (NH 3 , dimethyl sulfoxide, etc. will be condensed and returned to the reaction system to keep the concentration of each component in the reaction system relatively stable to avoid premature cessation of the reaction or reduction in yield due to a decrease in the concentration of the reactants). The magnetic stirrer is stirred at a speed of 200-300rpm for 4-12h to allow the γ-polyglutamic acid, alcohol derivatives and gardenia glycoside crosslinking agent in the system to fully undergo esterification and crosslinking reactions. Within the temperature range of 60-100°C, the reaction system obtains sufficient energy to allow the reactant molecules (γ-polyglutamic acid, alcohol derivatives and gardenia glycoside crosslinking agent) to have higher activation energy, thereby increasing the frequency of effective collisions. A sufficiently long reaction time can ensure that the reaction is fully carried out, so that the equilibrium moves toward the product direction, and the yield of γ-polyglutamate is increased as much as possible.
[0014] The hydroxyl group of Gardenia glycoside reacts with the remaining carboxyl group of γ-polyglutamic acid or the active site near the formed ester bond, and also reacts with other active sites of alcohol derivatives, thereby cross-linking γ-polyglutamic acid and alcohol derivatives through Gardenia glycoside. This cross-linking reaction can make γ-polyglutamate form a three-dimensional network structure, enhancing the physical and chemical properties of the material;
[0015] S1.6. After the reaction is completed, the reaction liquid is cooled to room temperature, and sodium hydroxide solution is slowly added to neutralize the acidic substances in the reaction liquid until the pH of the reaction liquid reaches neutrality; the esterification reaction is a reversible reaction, and acidic substances will be produced during the reaction. In an acidic environment, the ester bond may be attacked and broken, resulting in product decomposition. Neutralizing the reaction liquid to neutrality can avoid this acid-catalyzed hydrolysis reaction, ensure the stability of γ-polyglutamate, and ensure that the structure of the obtained product is intact;
[0016] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted alcohol derivatives, catalysts and dimethyl sulfoxide solvent;
[0017] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at a drying temperature of 40-60° C. for 12-24 hours until dry γ-polyglutamate is obtained.
[0018] After alcohols are aminated with glycine, an amino group (-NH 2 ) functional groups to obtain alcohol derivatives; alcohol derivatives have multiple hydroxyl groups (-OH), while there are a large number of carboxyl groups (-COOH) on the γ-polyglutamic acid molecular chain. In the esterification reaction, the hydroxyl groups of the alcohol derivatives and the carboxyl groups of γ-polyglutamic acid undergo a dehydration condensation reaction to form an ester bond (-COO-); due to the introduction of the ester bond, the hydrophilicity of the molecule will be reduced and the hydrophobicity will be relatively increased; the presence of the ester bond reduces the rigidity of the molecular chain and increases the flexibility. The original molecular chain of γ-polyglutamic acid is relatively hard. After esterification with alcohol compounds, the molecular chain can bend and stretch more freely; and the ester bond can also undergo a hydrolysis reaction under certain environmental conditions (such as under the action of microorganisms or specific chemicals), thereby gradually degrading the material;
[0019] The hydroxyl group of the gardenia glycoside crosslinker reacts with the active sites near the ester bond that has been formed in γ-polyglutamic acid (such as the hydrogen atom on the carbon atom next to the ester bond, etc.) or the unreacted carboxyl group. At the same time, the hydroxyl group of gardenia glycoside will also react with the active sites on the alcohol derivatives (such as the unreacted hydroxyl group or the hydrogen atom on the carbon atom adjacent to the hydroxyl group, etc.) to form a more complex three-dimensional network structure. Through esterification crosslinking modification, the physical properties of γ-polyglutamic acid, such as hydrophobicity, mechanical properties and degradability, can be significantly improved.
[0020] Preferably, in S1.4, the temperature of the magnetic stirrer is set to 60-100° C., and the stirring is continued at a speed of 200-400 rpm for 4-12 hours.
[0021] Preferably, in S1.6, the concentration of the sodium hydroxide solution is 0.5-1 mol / L, the dripping speed is 10-20 drops / minute, and the solution is neutralized to a pH of 6.5-7.5.
[0022] Preferably, the alcohol is any one of n-butanol or propylene glycol.
[0023] Preferably, the catalyst is any one of p-toluenesulfonic acid or citric acid.
[0024] Preferably, the specific preparation steps of the degradable material are:
[0025] S2.1. Weigh the following raw materials in parts by weight respectively: 30-50 parts by weight of polycaprolactone, 10-20 parts by weight of γ-polyglutamate, 5-10 parts by weight of microbial agent, 20-30 parts by weight of bentonite, and 10-20 parts by weight of pure wood fiber;
[0026] S2.2, place the pure wood fiber in a magnetic stirrer, add sodium hydroxide solution, and continue stirring to remove impurities and wax on the surface, then rinse with clean water until neutral, and dry for later use;
[0027] Meanwhile, grind the bentonite into fine powder and sieve it through 80-100 mesh to remove impurities.
[0028] S2.3, inoculating the microbial agent into the beef extract peptone medium to activate the bacteria, so that the microorganisms are in the logarithmic growth phase;
[0029] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber are mixed, placed in a magnetic stirrer, the magnetic stirrer is set at a temperature of 60-100° C., and stirred at a speed of 150-200 rpm for 15-20 minutes to obtain a mixed solution;
[0030] S2.5. When the temperature of the mixed system in S2.4 is reduced to 30-50°C, add the microbial agent and bentonite, and continue stirring for 10-15 minutes to evenly disperse the microbial agent and bentonite in the system;
[0031] S2.6, coating the mixed solution evenly on the substrate, and maintaining the coated material under a pressure of 5-10 MPa for 30-60 min to obtain a degradable material for mine ecological restoration;
[0032] Preferably, the concentration of the sodium hydroxide solution in S2.2 is 0.5-1 mol / L, the temperature of the magnetic stirrer is set to 20-30°C, and the stirring is continued at a speed of 200-400 rpm for 2-3 hours.
[0033] Preferably, the microbial agent is Bacillus subtilis or Aztec.
[0034] Microbial agents can secrete a variety of enzymes, such as proteases, lipases, cellulases, etc. These enzymes can help degrade organic pollutants in the soil, and can also help fix heavy metal ions in the soil through biosorption, reducing their mobility and toxicity; and can also directly or indirectly promote plant growth and development by producing plant growth hormone analogues, dissolving phosphorus and potassium minerals, etc.
[0035] Preferably, the microbial inoculum in S2.3 is cultured in a constant temperature incubator for 24-48 hours, for example, in a 37° C. constant temperature incubator.
[0036] In another aspect, the present invention provides a method for mine ecological restoration.
[0037] The method comprises using the degradable material as described above (degradable material for mine ecological restoration) to carry out ecological modification.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) In the degradable material for mine ecological restoration provided by the present invention, γ-polyglutamate prepared by esterification and cross-linking modification of alcohol derivatives and γ-polyglutamic acid is used as the degradable material; due to the introduction of ester bonds, the hydrophilicity of the molecules is reduced, the hydrophobicity is relatively increased, and the molecular chains can bend and stretch more freely; and the ester bonds can undergo hydrolysis reaction under certain environmental conditions (such as under the action of microorganisms or specific chemicals), thereby gradually degrading the material.
[0040] (2) The present invention utilizes the hydroxyl groups of the gardenia glycoside crosslinker to react with the active sites on γ-polyglutamic acid and alcohol derivatives (such as hydrogen atoms on carbon atoms next to ester bonds) to form a more complex three-dimensional network structure; through esterification crosslinking modification, the physical properties of γ-polyglutamate, such as hydrophobicity, mechanical properties and degradability, can be significantly improved.
[0041] (3) The present invention provides a new type of ecological restoration material, which is degradable and will not pollute the soil environment. It can also degrade organic pollutants in the soil, adsorb and solidify heavy metal ions, improve the soil, and promote the natural recovery of the soil.
[0042] (4) The present invention helps solve the soil pollution problem in mining areas, helps achieve ecological restoration and improvement in mining areas, and has broad application prospects. DETAILED DESCRIPTION
[0043] Hereinafter, a degradable material for mine ecological restoration and a mine ecological restoration method of the present invention will be described in detail in conjunction with exemplary embodiments.
[0044] The present invention provides a degradable material for mine ecological restoration, which is prepared from the following raw materials in parts by weight: 30-50 parts by weight of polycaprolactone, 10-20 parts by weight of gamma-polyglutamate, 5-10 parts by weight of microbial agent, 20-30 parts by weight of bentonite and 10-20 parts by weight of pure wood fiber;
[0045] The γ-polyglutamate is prepared by esterifying and cross-linking γ-polyglutamic acid with an alcohol derivative, and the mass ratio of γ-polyglutamic acid to the alcohol derivative is 1:1-3.
[0046] The alcohol is propylene glycol;
[0047] The catalyst is p-toluenesulfonic acid;
[0048] The microbial agent is any one of Bacillus subtilis or Aztec bacteria;
[0049] The microbial agent is preferably Bacillus subtilis;
[0050] Embodiment 1: A degradable material for mine ecological restoration, comprising the following steps:
[0051] S2.1. Weigh the following raw materials in parts by weight respectively: 40 parts by weight of polycaprolactone, 15 parts by weight of γ-polyglutamate, 8 parts by weight of Bacillus subtilis, 25 parts by weight of bentonite, and 13 parts by weight of pure wood fiber;
[0052] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0053] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0054] S2.3, inoculate Bacillus subtilis into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0055] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0056] S2.5. When the temperature of the mixed system in S2.4 is lowered to 35°C, add Bacillus subtilis and bentonite, and continue stirring for 15 minutes to evenly disperse the Bacillus subtilis and bentonite in the system;
[0057] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0058] Wherein, the specific preparation method of the γ-polyglutamate is:
[0059] S1.1, respectively weigh the following raw materials in parts by weight: 15 parts by weight of γ-polyglutamic acid, 15 parts by weight of propylene glycol-glycine ester, 2 parts by weight of p-toluenesulfonic acid catalyst, 8 parts by weight of glycine, 2 parts by weight of gardenia glycoside crosslinking agent, and 15 parts by weight of dimethyl sulfoxide solvent;
[0060] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0061] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0062] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add p-toluenesulfonic acid catalyst and gardenia glycoside crosslinker at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0063] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 12 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0064] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0065] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0066] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0067] Embodiment 2: A degradable material for mine ecological restoration, comprising the following steps:
[0068] S2.1. Weigh the following raw materials in parts by weight respectively: 40 parts by weight of polycaprolactone, 15 parts by weight of γ-polyglutamate, 8 parts by weight of Bacillus subtilis, 25 parts by weight of bentonite, and 13 parts by weight of pure wood fiber;
[0069] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0070] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0071] S2.3, inoculate Bacillus subtilis into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0072] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0073] S2.5. When the temperature of the mixed system in S2.4 is lowered to 35°C, add Bacillus subtilis and bentonite, and continue stirring for 15 minutes to evenly disperse the Bacillus subtilis and bentonite in the system;
[0074] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0075] Wherein, the specific preparation method of the γ-polyglutamate is:
[0076] S1.1, respectively weigh the following raw materials in parts by weight: 15 parts by weight of γ-polyglutamic acid, 30 parts by weight of propylene glycol-glycine ester, 2 parts by weight of p-toluenesulfonic acid catalyst, 8 parts by weight of glycine, 2 parts by weight of gardenia glycoside crosslinking agent, and 15 parts by weight of dimethyl sulfoxide solvent;
[0077] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0078] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0079] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add p-toluenesulfonic acid catalyst and gardenia glycoside crosslinker at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0080] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 12 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0081] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0082] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0083] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0084] Embodiment 3: A degradable material for mine ecological restoration, comprising the following steps:
[0085] S2.1. Weigh the following raw materials in parts by weight respectively: 40 parts by weight of polycaprolactone, 15 parts by weight of γ-polyglutamate, 8 parts by weight of Bacillus subtilis, 25 parts by weight of bentonite, and 13 parts by weight of pure wood fiber;
[0086] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0087] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0088] S2.3, inoculate Bacillus subtilis into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0089] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0090] S2.5. When the temperature of the mixed system in S2.4 is lowered to 35°C, add Bacillus subtilis and bentonite, and continue stirring for 15 minutes to evenly disperse the Bacillus subtilis and bentonite in the system;
[0091] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0092] Wherein, the specific preparation method of the γ-polyglutamate is:
[0093] S1.1, weigh the following raw materials in parts by weight respectively: 15 parts by weight of γ-polyglutamic acid, 45 parts by weight of propylene glycol-glycine ester, 2 parts by weight of p-toluenesulfonic acid catalyst, 8 parts by weight of glycine, 2 parts by weight of gardenia glycoside crosslinking agent, and 15 parts by weight of dimethyl sulfoxide solvent;
[0094] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0095] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0096] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add p-toluenesulfonic acid catalyst and gardenia glycoside crosslinker at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0097] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 12 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0098] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0099] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0100] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0101] Embodiment 4: A degradable material for mine ecological restoration, comprising the following steps:
[0102] S2.1. Weigh the following raw materials in parts by weight respectively: 40 parts by weight of polycaprolactone, 15 parts by weight of γ-polyglutamate, 8 parts by weight of Bacillus subtilis, 25 parts by weight of bentonite, and 13 parts by weight of pure wood fiber;
[0103] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0104] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0105] S2.3, inoculate Bacillus subtilis into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0106] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0107] S2.5. When the temperature of the mixed system in S2.4 is lowered to 35°C, add Bacillus subtilis and bentonite, and continue stirring for 15 minutes to evenly disperse the Bacillus subtilis and bentonite in the system;
[0108] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0109] Wherein, the specific preparation method of the γ-polyglutamate is:
[0110] S1.1, weigh the following raw materials in parts by weight respectively: 20 parts by weight of γ-polyglutamic acid, 10 parts by weight of propylene glycol-glycine ester, 2 parts by weight of p-toluenesulfonic acid catalyst, 8 parts by weight of glycine, 2 parts by weight of gardenia glycoside crosslinking agent, and 15 parts by weight of dimethyl sulfoxide solvent;
[0111] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0112] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0113] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add p-toluenesulfonic acid catalyst and gardenia glycoside crosslinker at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0114] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 12 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0115] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0116] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0117] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0118] Embodiment 5: A degradable material for mine ecological restoration, comprising the following steps:
[0119] S2.1. Weigh the following raw materials in parts by weight respectively: 40 parts by weight of polycaprolactone, 15 parts by weight of γ-polyglutamate, 5 parts by weight of Bacillus subtilis, 20 parts by weight of bentonite, and 10 parts by weight of pure wood fiber;
[0120] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0121] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0122] S2.3, inoculate Bacillus subtilis into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0123] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0124] S2.5. When the temperature of the mixed system in S2.4 is lowered to 35°C, add Bacillus subtilis and bentonite, and continue stirring for 15 minutes to evenly disperse the Bacillus subtilis and bentonite in the system;
[0125] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0126] Wherein, the specific preparation method of the γ-polyglutamate is:
[0127] S1.1, respectively weigh the following raw materials in parts by weight: 15 parts by weight of γ-polyglutamic acid, 30 parts by weight of propylene glycol-glycine ester, 2 parts by weight of p-toluenesulfonic acid catalyst, 8 parts by weight of glycine, 2 parts by weight of gardenia glycoside crosslinking agent, and 15 parts by weight of dimethyl sulfoxide solvent;
[0128] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0129] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0130] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add p-toluenesulfonic acid catalyst and gardenia glycoside crosslinker at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0131] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 12 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0132] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0133] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0134] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0135] Embodiment 6: A degradable material for mine ecological restoration, comprising the following steps:
[0136] S2.1. Weigh the following raw materials in parts by weight respectively: 40 parts by weight of polycaprolactone, 10 parts by weight of γ-polyglutamate, 5 parts by weight of Bacillus subtilis, 20 parts by weight of bentonite, and 10 parts by weight of pure wood fiber;
[0137] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0138] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0139] S2.3, inoculate Bacillus subtilis into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0140] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0141] S2.5. When the temperature of the mixed system in S2.4 is lowered to 35°C, add Bacillus subtilis and bentonite, and continue stirring for 15 minutes to evenly disperse the Bacillus subtilis and bentonite in the system;
[0142] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0143] Wherein, the specific preparation method of the γ-polyglutamate is:
[0144] S1.1, respectively weigh the following raw materials in parts by weight: 15 parts by weight of γ-polyglutamic acid, 30 parts by weight of propylene glycol-glycine ester, 2 parts by weight of p-toluenesulfonic acid catalyst, 8 parts by weight of glycine, 2 parts by weight of gardenia glycoside crosslinking agent, and 15 parts by weight of dimethyl sulfoxide solvent;
[0145] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0146] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0147] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add the catalyst and the gardenia glycoside cross-linking agent at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0148] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 12 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0149] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0150] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0151] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0152] Embodiment 7: A degradable material for mine ecological restoration, comprising the following steps:
[0153] S2.1. Weigh the following raw materials in parts by weight respectively: 40 parts by weight of polycaprolactone, 20 parts by weight of γ-polyglutamate, 5 parts by weight of Bacillus subtilis, 20 parts by weight of bentonite, and 10 parts by weight of pure wood fiber;
[0154] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0155] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0156] S2.3, inoculate Bacillus subtilis into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0157] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0158] S2.5. When the temperature of the mixed system in S2.4 is lowered to 35°C, add Bacillus subtilis and bentonite, and continue stirring for 15 minutes to evenly disperse the Bacillus subtilis and bentonite in the system;
[0159] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0160] Wherein, the specific preparation method of the γ-polyglutamate is:
[0161] S1.1, respectively weigh the following raw materials in parts by weight: 15 parts by weight of γ-polyglutamic acid, 30 parts by weight of propylene glycol-glycine ester, 2 parts by weight of p-toluenesulfonic acid catalyst, 8 parts by weight of glycine, 2 parts by weight of gardenia glycoside crosslinking agent, and 15 parts by weight of dimethyl sulfoxide solvent;
[0162] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0163] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0164] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add the catalyst and the gardenia glycoside cross-linking agent at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0165] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 12 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0166] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0167] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0168] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0169] Embodiment 8: A degradable material for mine ecological restoration, comprising the following steps:
[0170] S2.1. Weigh the following raw materials in parts by weight respectively: 40 parts by weight of polycaprolactone, 15 parts by weight of γ-polyglutamate, 8 parts by weight of Bacillus subtilis, 25 parts by weight of bentonite, and 13 parts by weight of pure wood fiber;
[0171] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0172] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0173] S2.3, inoculate Bacillus subtilis into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0174] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0175] S2.5. When the temperature of the mixed system in S2.4 is lowered to 35°C, add Bacillus subtilis and bentonite, and continue stirring for 15 minutes to evenly disperse the Bacillus subtilis and bentonite in the system;
[0176] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0177] Wherein, the specific preparation method of the γ-polyglutamate is:
[0178] S1.1, weigh the following raw materials in parts by weight respectively: 15 parts by weight of γ-polyglutamic acid, 30 parts by weight of propylene glycol-glycine ester, 2 parts by weight of p-toluenesulfonic acid catalyst, 8 parts by weight of glycine, 3 parts by weight of gardenia glycoside crosslinking agent, and 15 parts by weight of dimethyl sulfoxide solvent;
[0179] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0180] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0181] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add p-toluenesulfonic acid catalyst and gardenia glycoside crosslinker at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0182] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 12 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0183] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0184] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0185] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0186] Embodiment 9: A degradable material for mine ecological restoration, comprising the following steps:
[0187] S2.1. Weigh the following raw materials in parts by weight respectively: 40 parts by weight of polycaprolactone, 15 parts by weight of γ-polyglutamate, 8 parts by weight of Bacillus subtilis, 25 parts by weight of bentonite, and 13 parts by weight of pure wood fiber;
[0188] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0189] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0190] S2.3, inoculate Bacillus subtilis into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0191] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0192] S2.5. When the temperature of the mixed system in S2.4 is lowered to 35°C, add Bacillus subtilis and bentonite, and continue stirring for 15 minutes to evenly disperse the Bacillus subtilis and bentonite in the system;
[0193] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0194] Wherein, the specific preparation method of the γ-polyglutamate is:
[0195] S1.1, weigh the following raw materials in parts by weight respectively: 15 parts by weight of γ-polyglutamic acid, 30 parts by weight of propylene glycol-glycine ester, 2 parts by weight of p-toluenesulfonic acid catalyst, 8 parts by weight of glycine, 1 part by weight of gardenia glycoside crosslinking agent, and 15 parts by weight of dimethyl sulfoxide solvent;
[0196] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0197] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0198] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add p-toluenesulfonic acid catalyst and gardenia glycoside crosslinker at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0199] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 6 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0200] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0201] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0202] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0203] Embodiment 10: A degradable material for mine ecological restoration, comprising the following steps:
[0204] S2.1. Weigh the following raw materials in parts by weight respectively: 30 parts by weight of polycaprolactone, 15 parts by weight of γ-polyglutamate, 8 parts by weight of Aztec bacteria, 25 parts by weight of bentonite, and 13 parts by weight of pure wood fiber;
[0205] S2.2, place the pure wood fiber in a magnetic stirrer, add 0.5 mol / L sodium hydroxide solution, set the temperature of the magnetic stirrer to 30°C, stir at a speed of 300 rpm for 3 hours to remove surface impurities and wax, then rinse with clean water until neutral, and dry for later use;
[0206] Meanwhile, grind the bentonite into fine powder and sieve it through 100 mesh to remove impurities;
[0207] S2.3, inoculate Aztec bacteria into beef extract peptone medium for bacterial activation, and culture in a 37°C constant temperature incubator for 48 hours to keep the microorganisms in the logarithmic growth phase;
[0208] S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber were mixed, placed in a magnetic stirrer, the temperature of the magnetic stirrer was set to 60°C, and stirred at a speed of 200 rpm for 20 minutes to obtain a mixed solution;
[0209] S2.5, when the temperature of the mixed system in S2.4 is reduced to 35°C, add Aztec bacteria and bentonite, and continue stirring for 15 minutes to evenly disperse Aztec bacteria and bentonite in the system;
[0210] S2.6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 10 MPa for 60 minutes to obtain a degradable material for mine ecological restoration.
[0211] Wherein, the specific preparation method of the γ-polyglutamate is:
[0212] S1.1, weigh the following raw materials in parts by weight respectively: 15 parts by weight of γ-polyglutamic acid, 30 parts by weight of propylene glycol-glycine ester, 1 part by weight of p-toluenesulfonic acid catalyst, 5 parts by weight of glycine, 2 parts by weight of gardenia glycoside crosslinking agent, and 10 parts by weight of dimethyl sulfoxide solvent;
[0213] S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, and placing in a magnetic stirrer, setting the temperature of the magnetic stirrer to 65°C, stirring at a speed of 300 rpm for 2 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution;
[0214] S1.3, dissolving propylene glycol in glycine, placing in a magnetic stirrer, and adjusting the pH to 9 with 0.5 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 60°C, stirring at a speed of 300 rpm for 3 h to obtain propylene glycol-glycine ester;
[0215] S1.4, add propylene glycol-glycine ester to the γ-polyglutamic acid solution at a rate of 10 drops / min, add p-toluenesulfonic acid catalyst and gardenia glycoside crosslinker at the same time, and keep stirring; set the temperature of the magnetic stirrer to 80°C, and stir at a speed of 300 rpm for 6 hours;
[0216] S1.5, heating the mixed solution of S1.4 at 100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 300 rpm for 12 hours, so that the γ-polyglutamic acid, propylene glycol-glycine ester and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction;
[0217] S1.6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; the concentration of the sodium hydroxide solution is 0.5 mol / L, and the dropping speed is 10 drops / minute, and the pH is neutralized to 7;
[0218] S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted propylene glycol-glycine ester, p-toluenesulfonic acid catalyst and dimethyl sulfoxide solvent;
[0219] S1.8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at 60°C for 24 hours until dry γ-polyglutamate is obtained.
[0220] Comparative Example 1: The method of Example 2 was adopted, but the alcohol derivatives were not used to perform esterification and cross-linking co-modification on the γ-polyglutamic acid.
[0221] Comparative Example 2: The method of Example 2 was used to remove the gardenia glycoside cross-linking agent during the esterification cross-linking process.
[0222] The degradable material for mine ecological restoration prepared by γ-polyglutamate in the present invention has good mechanical properties and degradability, wherein the performance index inspection items and inspection standards of the degradable material are as follows:
[0223] The maximum stress that a material can withstand until it breaks is measured by a standard tensile testing machine. The unit is megapascal (MPa), which reflects the material's ability to resist tensile failure. It is the ratio of the elongated length of the specimen to the original length when the material breaks. It is usually expressed as a percentage. A high elongation indicates that the material can withstand a large deformation before breaking, that is, it has good flexibility and ductility.
[0224] Degradation rate of degradable materials is determined according to GB / T 41010-2021 standard. First, the initial mass of the material is weighed, and then it is degraded in a specified environment (such as compost or soil) and conditions (such as specific temperature and humidity). After the predetermined time, the material is taken out, the attachments are removed, and it is dried to a constant weight and weighed again. The degradation rate is calculated by comparing the initial and post-degradation masses, and the observation results are recorded to evaluate its degradation performance.
[0225] The degradable materials prepared in the above examples 1-10 and comparative examples 1-2 were tested according to the above standards, and the obtained data are shown in Table 1:
[0226] Table 1 Performance data of degradable materials of Examples 1-10 and Comparative Examples 1-2
[0227] Implementation / Comparative Example Elongation % Degradation rate % Example 1 39.8 84.8 Example 2 43.6 88.6 Example 3 45.3 90.2 Example 4 40.6 85.4 Example 5 43.3 88.1 Example 6 41.6 86.5 Example 7 46.4 91.4 Example 8 41.9 86.9 Example 9 40.2 85.2 Example 10 42.7 87.3 Comparative Example 1 20.8 64.9 Comparative Example 2 26.3 70.1
[0228] The above data fully show that Examples 1-10 are compared with Comparative Examples 1-2, wherein the degradation rate is a physical quantity that measures the degradation ability of a material under specific conditions. The higher the degradation rate, the greater the degree to which the material is decomposed within a given time, which means that the material is more easily or quickly decomposed into simpler substances such as water, carbon dioxide and biomass by microorganisms or other natural factors in the environment (such as soil, water or composting environment); conversely, if the degradation rate is low, it means that the material is less decomposed within a given time, that is, the material is more difficult or slower to be decomposed by microorganisms or other natural factors in the environment, as follows:
[0229] It can be seen from Examples 1-4 that: when the mass ratio of alcohol derivatives to γ-polyglutamic acid in γ-polyglutamate gradually increases, the various physical properties of the degradable material gradually increase, but when the mass ratio of alcohol derivatives to γ-polyglutamic acid reaches a certain value, the increase rate of the physical properties significantly decreases. It can be seen that by adjusting the mass ratio of alcohol derivatives to γ-polyglutamic acid, the structure and properties of γ-polyglutamate can be regulated. As the proportion of alcohol derivatives increases, the various physical properties of the material are improved, but excessive increase may reduce the mechanical strength and degradation rate of the material.
[0230] Specifically, alcohol derivatives have multiple hydroxyl groups (-OH), while γ-polyglutamic acid has a large number of carboxyl groups (-COOH) on the molecular chain. In the esterification reaction, the hydroxyl groups of the alcohol derivatives react with the carboxyl groups of γ-polyglutamic acid to form ester bonds (-COO-). The ester bonds can enhance the intermolecular forces, thereby possibly improving the mechanical strength and rigidity of the material; and the ester bonds can be broken by hydrolases or other hydrolysis processes, thereby gradually degrading the material.
[0231] Furthermore, by comparing Example 5, Example 6 and Example 7, it can be seen that when the other components remain unchanged, only when the proportion of γ-polyglutamate gradually increases, the various physical performance data of the degradable material are significantly improved. It can be seen that as the γ-polyglutamate increases and the ester bonds increase, the interaction force between molecules is enhanced, the network structure is tighter, and a more stable three-dimensional network structure is formed, which enhances the mechanical strength and toughness of the material; at the same time, the ester bonds are more easily recognized and broken by hydrolases or other biodegradation factors in the degradation environment, thereby increasing the degradation rate of the material; and the introduction of γ-polyglutamate may optimize the microstructure of the material, making it more uniform and consistent, and reducing defects, which is beneficial to improving the mechanical properties and also helps to evenly disperse the stress during the degradation process, avoiding uneven degradation caused by local stress concentration.
[0232] Combining Examples 5-7 with Comparative Example 1, it can be seen that when the γ-polyglutamic acid is not modified by esterification and cross-linking with alcohol derivatives, the physical properties of the degradable material are significantly reduced.
[0233] Furthermore, by comparing Example 2, Example 8 and Example 9, it can be seen that when the other components in the γ-polyglutamate remain unchanged, only when the proportion of the gardenia glycoside cross-linking agent gradually increases, the physical properties of the degradable material are stably improved;
[0234] And taking Example 2 as the best example, combined with Comparative Example 2, it can be seen that in the preparation method of γ-polyglutamate, when the gardenia glycoside cross-linking agent is removed, the physical properties of the degradable material are significantly reduced;
[0235] Among them, the active groups in the gardenia glycoside crosslinker, such as phenolic hydroxyl (-OH), can form chemical bonds or hydrogen bonds with functional groups in γ-polyglutamate, such as carboxyl (-COOH) or ester (-COOR), thereby establishing a crosslinking network between molecules; the formation of the crosslinking network increases the cohesion of the material, so that when the material is subjected to external force, the stress can be more evenly distributed in the entire material system, thereby improving the mechanical strength and toughness of the material; the presence of crosslinking points limits the free movement of polymer molecular chains, making the material less likely to soften or flow at high temperatures, thereby improving thermal stability; the presence of the crosslinking structure requires the material to break the crosslinking points first during the degradation process, and then further degrade the polymer chain. Therefore, crosslinking can play a role in regulating the degradation rate, so that the material can degrade at the expected rate in a specific environment.
[0236] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A degradable material for mine ecological restoration, characterized by: Prepared from the following raw materials by weight: 30-50 parts by weight of polycaprolactone, 10-20 parts by weight of gamma-polyglutamate, 5-10 parts by weight of microbial agent, 20-30 parts by weight of bentonite and 10-20 parts by weight of pure wood fiber; The γ-polyglutamate is prepared by esterifying and cross-linking γ-polyglutamic acid with alcohol derivatives, and the mass ratio of γ-polyglutamic acid to the alcohol derivative is 1:1-3.
2. The degradable material for mine ecological restoration according to claim 1, characterized in that: The specific preparation method of the γ-polyglutamate is as follows: S1.1, weigh the following raw materials in parts by weight respectively: 10-20 parts by weight of γ-polyglutamic acid, 10-60 parts by weight of alcohol derivatives, 1-3 parts by weight of catalysts, 5-10 parts by weight of glycine, 1-3 parts by weight of gardenia glycoside crosslinking agent, and 10-20 parts by weight of dimethyl sulfoxide solvent; S1.2, dissolving γ-polyglutamic acid in dimethyl sulfoxide solvent, setting the temperature of the magnetic stirrer to 50-80°C, stirring at a speed of 200-500 rpm for 1-3 hours, and stirring thoroughly until the γ-polyglutamic acid is completely dissolved to obtain a γ-polyglutamic acid solution; S1.3, dissolving the alcohol in glycine, placing in a magnetic stirrer, and adjusting the pH of the mixed solution of the alcohol and glycine to 9-10 with 0.5-1 mol / L sodium hydroxide solution, setting the temperature of the magnetic stirrer to 30-60°C, stirring at a speed of 200-400 rpm for 2-4 hours to obtain an alcohol derivative; S1.4, add the alcohol derivative to the γ-polyglutamic acid solution at a rate of 10-20 drops / min, add the catalyst and the gardenia glycoside cross-linking agent at the same time, and keep stirring; S1.5, heating the mixed solution of S1.4 at 60-100°C for reflux reaction, stirring with a magnetic stirrer at a speed of 200-300 rpm for 4-12 hours, so that the γ-polyglutamic acid, alcohol derivatives and gardenia glycoside cross-linking agent in the system can fully undergo esterification and cross-linking reaction; S1.
6. After the reaction is completed, the reaction solution is cooled to room temperature, and sodium hydroxide solution is slowly added dropwise to neutralize the acidic substances in the reaction solution until the pH of the reaction solution reaches neutral; S1.7, pouring the neutralized reaction solution into anhydrous ethanol to precipitate γ-polyglutamate, filtering the precipitate, and washing the γ-polyglutamate precipitate with anhydrous ethanol for multiple times to remove unreacted alcohol derivatives, catalysts and dimethyl sulfoxide solvent; S1.
8. Place the washed γ-polyglutamate precipitate in a vacuum drying oven at a drying temperature of 40-60° C. for 12-24 hours until dry γ-polyglutamate is obtained.
3. The degradable material for mine ecological restoration according to claim 2, characterized in that: In S1.4, the temperature of the magnetic stirrer is set to 60-100° C., and the stirring is continued at a speed of 200-400 rpm for 4-12 hours.
4. The degradable material for mine ecological restoration according to claim 2, characterized in that: In the S1.6, the concentration of the sodium hydroxide solution is 0.5-1 mol / L, the dropping speed is 10-20 drops / minute, and the solution is neutralized to a pH of 6.5-7.
5.
5. The degradable material for mine ecological restoration according to claim 2, characterized in that: The alcohol is any one of n-butanol or propylene glycol.
6. The degradable material for mine ecological restoration according to claim 2, characterized in that: The catalyst is any one of p-toluenesulfonic acid or citric acid.
7. The degradable material for mine ecological restoration according to claim 1, characterized in that: The specific preparation steps of the degradable material are: S2.
1. Weigh the following raw materials in parts by weight respectively: 30-50 parts by weight of polycaprolactone, 10-20 parts by weight of γ-polyglutamate, 5-10 parts by weight of microbial agent, 20-30 parts by weight of bentonite, and 10-20 parts by weight of pure wood fiber; S2.2, place the pure wood fiber in a magnetic stirrer, add sodium hydroxide solution, and continue stirring to remove impurities and wax on the surface, then rinse with clean water until neutral, and dry for later use; Meanwhile, grind the bentonite into fine powder and sieve it through 80-100 mesh to remove impurities; S2.3, inoculating the microbial agent into the beef extract peptone medium to activate the bacteria, so that the microorganisms are in the logarithmic growth phase; S2.4, polycaprolactone, γ-polyglutamate and pure wood fiber are mixed, placed in a magnetic stirrer, the magnetic stirrer is set at a temperature of 60-100° C., and stirred at a speed of 150-200 rpm for 15-20 minutes to obtain a mixed solution; S2.
5. When the temperature of the mixed system in S2.4 is reduced to 30-50°C, add the microbial agent and bentonite, and continue stirring for 10-15 minutes to evenly disperse the microbial agent and bentonite in the system; S2.
6. The mixed solution is evenly coated on the substrate, and the coated material is kept under a pressure of 5-10 MPa for 30-60 min to obtain a degradable material for mine ecological restoration.
8. The degradable material for mine ecological restoration according to claim 7, characterized in that: The concentration of the sodium hydroxide solution in S2.2 is 0.5-1 mol / L, the temperature of the magnetic stirrer is set to 20-30°C, and stirring is continued at a speed of 200-400 rpm for 2-3 hours.
9. The degradable material for mine ecological restoration according to claim 7, characterized in that: The microbial agent is any one of Bacillus subtilis and Aztecia; The microbial inoculum in S2.3 is placed in a constant temperature incubator and cultured for 24-48 hours.
10. A method for mine ecological restoration, characterized in that: The method comprises ecological modification using the material of any one of claims 1 to 9.
Citation Information
Patent Citations
Polyester urethane
JP2003335837A
Cited By
High and cold mining area plant stress-resistant microbial agent as well as preparation method and application thereof
CN120555273A
Gardenoside granules for soil remediation and preparation method thereof
CN122483801A